Characterization of heme binding to recombinant α1-microglobulin - Karnaukhova, Elena; Rutardottir, Sigurbjörg; Rajabi, Mohsen; Wester Rosenlöf, Lena; Alayash, Abdu I.; Åkerström, Bo (Frontiers in Physiology, 2014)
Background: Alpha-1-microglobulin (A1M), a small lipocalin protein found in plasma and tissues, has been identified as a heme and radical scavenger that may participate in the mitigation of toxicities caused by degradation of hemoglobin. The objective of this work was to investigate heme interactions with A1M in vitro using various analytical techniques and to optimize analytical methodology suitable for rapid evaluation of the ligand binding properties of recombinant A1M versions. Methods: To examine heme binding properties of A1M we utilized UV/Vis absorption spectroscopy, visible circular dichroism (CD), catalase-like activity, migration shift electrophoresis, and surface plasmon resonance (SPR), which was specifically developed for the assessment of His-tagged A1M. Results: The results of this study confirm that A1M is a heme binding protein that can accommodate heme at more than one binding site and/or in coordination with different amino acid residues depending upon heme concentration and ligand-to-protein molar ratio. UV/Vis titration of A1M with heme revealed an unusually large bathochromic shift, up to 38 nm, observed for heme binding to a primary binding site. UV/Vis spectroscopy, visible CD and catalase-like activity suggested that heme is accommodated inside His-tagged (tgA1M) and tagless A1M (ntA1M) in a rather similar fashion although the His-tag is very likely involved into coordination with iron of the heme molecule. SPR data indicated kinetic rate constants and equilibrium binding constants with KD values in a uM range. Conclusions: This study provided experimental evidence of the A1M heme binding properties by aid of different techniques and suggested an analytical methodology for a rapid evaluation of ligand-binding properties of recombinant A1M versions, also suitable for other His-tagged proteins.